THU0460 Fully integrated 18f-fdg pet/mr in large vessel vasculitis. (12th June 2018) - Padoan, R.; Crimì, F.; Felicetti, M.; Padovano, F.; Punzi, L.; Lacognata, C.; Stramare, R.; Cecchin, D.; Bui, F.; Zucchetta, P.; Schiavon, F.
Abstract : Background: Positron emission tomography (PET) is a non-invasive imaging method that detects 18 F-fluorodeoxyglucose (FDG) uptake in vessel's walls. Its simultaneous combination with magnetic resonance (MR) would offer not only a more detailed morphological analysis of the vessels but also a reduction of the radiation, simplifying the clinical workflow and being logistically easier for the patient. Objectives: To evaluate, for the first time up to now, the usefulness of a fully integrated 18F-FDG PET/MR in a series of large vessels vasculitides (LVV) patients. Methods: We performed a controlled non-randomised prospective study. Images were acquired on a fully integrated PET/MR scanner (Siemens Biograph mMR), consisting in a complete MR protocol and FDG-PET whole body imaging. We evaluated vessel's standard uptake value (SUV) maximum and wall thickness (WT), defined as the mean of 4 measures (at 12, 3, 6 and 9 o'clock) at the inferior margin of D5, D9, D12, L3 and at thickest point (max WT). Results: 23 LVV patients were included, 56.5% GCA, 34.8% TAK and 8.7% isolated aortitis, all Caucasian, mostly females (82%). We considered 55 PET scans, 32/55 in LVV group (from min. 1 to max. 3 scans/patient) mainly during follow-up (29/32 scans), and 23/55 in control group. Considering patients with abdominal aorta involvement, we found higher SUV max compared to controls, in all sites, regardless of disease activity. Mean WT resulted higher in patients than controls, but did not significantly differ between PET active or inactive patients (figure 1). Mean WT positively correlated with age in both cohorts, inversely correlated to disease duration in LVV patients, while no correlation with SUV max was observed. Despite clinical assessment was suggestive of remission in 24 (75%) cases before PET/MR acquisition, a normal uptake was present only in 12 (50%) of them. On the contrary, all patient with active disease at clinical examination (8, 25%) had also a positive PET/MR. Cohen's K coefficient between clinical assessment and imaging was poor (K Cohen=0, 33, 0.11–0.55). Finally, we found no significant correlation between SUV max and acute phase reactants. Demographic and clinical data of LVV patients. Conclusions: PET/MR is a safe imaging technique capable of detecting vasculitic inflammation, similar to PET/CT, but with a greater anatomical definition. The low radiological exposure represents a valid alternative to PET/CT for disease monitoring, especially in young women. Disclosure of Interest: None declared